The roots of the quadratic equations are -4 and -1
-2x^(2)-3x+4=0
Expand the equation first
[tex]-2(x^2 - 3x + 4) = 0[/tex]
Find two factor that are multiples of -8 and sum up to give -3, the facors are -4 and -1
Replace -3x with 4x and -x
[tex]-2(x^2 -4x + x + 4) = 0[/tex]
Factorize the equation
[tex]-2 (x (x + 4) + 1 (x + 4)[/tex]
We have
2(x + 1) = 0 and 2(x+ 4) = 0
2(x + 1) = 0
2x + 2 = 0
x = -1
2(x+ 4) = 0
2x + 8 = 0
x = -8/2
x = -4
Therefore, the roots of the quadratic equations are -4 and -1
Learn more about quadratic equations here:
https://brainly.com/question/1214333
#SPJ1